2018
DOI: 10.1002/jbio.201800028
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive optical method for real‐time assessment of intracorneal riboflavin concentration and efficacy of corneal cross‐linking

Abstract: Keratoconus is the primary cause of corneal transplantation in young adults worldwide. Riboflavin/UV-A corneal cross-linking may effectively halt the progression of keratoconus if an adequate amount of riboflavin enriches the corneal stroma and is photo-oxidated by UV-A light for generating additional cross-linking bonds between stromal proteins and strengthening the biomechanics of the weakened cornea. Here we reported an UV-A theranostic prototype device for performing corneal cross-linking with the ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…Kling et al) that oxygen-mediated type-II plays the critical role of CXL, Kamaev et al 8 kinetic model showed that CXL is predominated by type-I, while oxygen (or type-II) only plays a limited and transient role. Lin's 3-pathway model 9 showed mathematical details of the role of oxygen, supporting the claim of Kamaev et al 8 In addition, a recent clinical study of Lombardo et al 10 showed a simple-exponential kinetic of RF concentration also implied that, in ambient environment (with approximately 21% partial pressure of oxygen), nonoxygen-mediated type-I mechanism is predominant. 6.…”
Section: In Contrast To the Conventional Belief (By Hafezi Andmentioning
confidence: 57%
“…Kling et al) that oxygen-mediated type-II plays the critical role of CXL, Kamaev et al 8 kinetic model showed that CXL is predominated by type-I, while oxygen (or type-II) only plays a limited and transient role. Lin's 3-pathway model 9 showed mathematical details of the role of oxygen, supporting the claim of Kamaev et al 8 In addition, a recent clinical study of Lombardo et al 10 showed a simple-exponential kinetic of RF concentration also implied that, in ambient environment (with approximately 21% partial pressure of oxygen), nonoxygen-mediated type-I mechanism is predominant. 6.…”
Section: In Contrast To the Conventional Belief (By Hafezi Andmentioning
confidence: 57%
“…In contrast to the conventional belief that oxygen-mediated type-II plays the critical role of CXL, the kinetic model of Kamaev et al 6 showed that CXL is predominated by type-I, whereas oxygen (or type-II) plays only a limited and transient role. Lin's 3-pathway model 5,7 showed mathematical details of the role of oxygen, supporting the claim of Kamaev et al 6 Moreover, a recent clinical study of Lombardo et al 8 showed a simpleexponential temporal profile of Rf concentration that implied that, in ambient environment, non-oxygen-mediated type-I mechanism is predominant.…”
mentioning
confidence: 56%
“…In contrast to type-II (S2), in which oxygen plays a transient but critical role, type-I (S1) does not require oxygen and it is the predominant pathway of CXL efficacy. [4][5][6][7][8] At steady-state (with btX>>1), S1 follows a nonlinear scaling law 4 that S1 is proportional to (FC 0 /I 0 ) 0.5 exp(0.5Az), or S1a[C 0 ] 0.5 (for z ¼ 0) and stronger dependence of S1a[C 0 exp(Az)] 0.5 (for z > 0), because A is also proportional to C 0 . For example, on corneal surface (or z ¼ 0), when C 0 is doubled (from 0.1% to 0.2%), S1 increases by a factor of 1.43.…”
mentioning
confidence: 99%
“…Techniques that were used in a laboratory environment included spectrophotometry, high-performance liquid chromatography, confocal fluorescence microscopy, and two-photon optical microscopy, all of which involve some degree of invasiveness and are not readily translatable into a clinical setting. [55][56][57][58] To fill in this lacuna, Lombardo and colleagues 59 have recently developed a noninvasive optical method for real-time assessment of intrastromal riboflavin concentration which has the potential to be useful in delivering personalized C-CXL treatments.…”
Section: Advances In Treatmentmentioning
confidence: 99%